Copepods in turbid shallow soda lakes accumulate unexpected high levels of carotenoids. - Tobias Schneider; Alois Herzig; Karin A Koinig; Ruben Sommaruga (PLoS ONE, 2012)
Carotenoids are protective pigments present in many aquatic organisms that reduce the photooxidative stress induced by short-wavelenght solar radiation, yet increase their susceptibility to predators. Arctodiaptomus spinosus, a calanoid copepod typically found in many fishless shallow soda lakes, shows large between-lake differences in pigmentation. Here, we attribute these differences to the environmental state of these ecosystems, namely, 'dark water' lakes with submersed vegetation and turbid 'white' lakes lacking macrophytes. Copepod carotenoid concentration in the turbid 'white' lakes was significantly (about 20-fold) higher than in the 'dark water' ones, although the latter systems were characterized by higher transparency. In addition, males had on a dry weight basis around three times higher carotenoid concentrations than females. Mycosporine-like amino acids (direct UV screening substances) were found in all cases, but in low concentration. The environmental conditions in these ecosystems were largely shaped by the presence/absence of submersed macrophytes Thus, in the turbid lakes, the strong wind-driven mixis allows for copepods to be brought to the surface and being exposed to solar radiation, whereas in 'dark water' ones, macrophytes reduce water turbulence and additionally provide shelter. Our results explain the counter-intuitive notion of strong red pigmentation in copepods from a turbid ecosystem and suggest that factors other than high UV transparency favor carotenoid accumulation in zooplankton.